Sexually Transmitted Infection Related Stigma and Shame Among African American Male Youth: Implications for Testing Practices, Partner Notification, and Treatment - Morris, Jessica L. (Mary Ann Liebert, Inc., 2014)
A self-administered, street intercept survey was conducted in order to examine the relation of stigma and shame associated with sexually transmitted infections (STI) to STI testing practices, partner notification, and partner-delivered treatment among young African American men (n=108) in a low-income, urban community in San Francisco with high STI burden. Multivariate logistic regression revealed that increasing STI-related stigma was significantly associated with a decreased odds of STI testing, such that every standard deviation increase in stigma score was associated with 0.62 decreased odds of having been tested (aOR: 0.62, 95% CI: 0.38–1.00), controlling for age. STI stigma was also significantly associated with a decreased willingness to notify non-main partners of an STI (aOR: 0.64 95% CI: 0.41–0.99). Participants with higher levels of stigma and shame were also significantly less likely to be willing to deliver STI medication to a partner (stigma aOR: 0.57, 95% CI: 0.37–0.88; shame aOR 0.53 95% CI: 0.34–0.83). Findings suggest that STI-related stigma and shame, common in this population, could undermine STI testing, treatment, and partner notification programs. The medical establishment, one of the institutional factors to have reinforced this culture of stigma, must aid efforts to reduce its effects through providing integrated services, reframing sexual health in campaigns, educating clients, and providing wider options to aid disclosure and partner notification practices.